Microplastics and human health: unraveling the toxicological pathways and implications for public health - Zhang, Xu; Yu, Chunhong; Wang, Peng; Yang, Chunping (Frontiers in Public Health, 2025)
The increasing prevalence of microplastics (MPs) in the environment has raised urgent concerns regarding their implications for human health. This comprehensive review integrates recent findings on the sources, classification, and pathways of MPs into the human body, highlighting their potential cellular toxicity and systemic health risks. We discuss the mechanisms by which MPs may induce inflammatory responses, oxidative stress, and cellular damage, thereby contributing to various diseases. Notably, we examine the synergistic effects of MPs in conjunction with other environmental pollutants, which may amplify their adverse health outcomes. This synthesis of current research underscores the critical need for multidisciplinary approaches to investigate the multifaceted interactions between MPs and human health, ultimately guiding future studies and informing public health strategies to mitigate exposure and associated risks.